The effect of Islamic sacred months on stock prices in Iran and Iraq Stock Exchanges - Faisal Abduleh Salman Irag Al-Najaf; Mahdi Salehi; Hind Shafeeq Nimr Al-Maliki (ISRA International Journal of Islamic Finance, 2018)
Purpose: The present study aims to examine the effects of the Islamic sacred months, namely, Muḥarram, Rajab, Dhu al-Qaʿdah and Dhu al-Qaʿijjah, on stock prices on the Iran and Iraq Stock Exchanges. Design/methodology/approach Using the infrastructure models of the capital market, the daily stock prices were calculated for the sacred and non-sacred months. As the data of this study are non-stationary, the AMIRA time-series model was used for better understanding of the model or future projections. The dependent variables of this study are the daily stock indexes for Iranian and Iraqi Stock Exchanges, and independent ones are the sacred and non-sacred months of a lunar year. Data were gathered daily from the financial statements of Iranian and Iraqi Stock Exchanges websites. To test the hypotheses under study, a five-year period from 2012 to 2016 was considered for both Iraqi and Iranian Stock Exchanges, which corresponds with the lunar calendar from 1433-1437AH. Findings The obtained results indicated that there is no significant difference in stock prices between the sacred months of Muḥarram, Rajab, Dhu al-Qaʿdah and Dhu al-Qaʿijjah and other non-sacred months. However, the stock price in the Iranian Stock Exchange has a significant difference in Rajab and Dhu al-Qaʿdah with other non-sacred months. Originality/value The results of this study will reveal more than ever the role of Islamic sacred months for society and users of financial statements to make better financial decisions especially in Islamic emerging markets.
Keywords: 330; Calendar anomalies; Non-calendar anomalies; Sacred months; Stock price